Withdrawn and Acting out?: Early Adolescents' Social Avoidance and Externalizing Problems. (6th July 2021) - Clifford, Brandon Neil; Eggum, Natalie D.; An, Danming; Clifford, Sierra; Lemery‐Chalfant, Kathryn
Abstract : Relative to other motivations of social withdrawal (i.e., shyness, unsociability), social avoidance is understudied. Furthermore, the relation between social avoidance and externalizing problems seldom has been investigated despite reasons to expect an association. We examined the association between social avoidance and externalizing problems using a sample of early adolescents in the United States using parents' reports ( N = 294; 54.1% boys; M age = 12.43 years). Supporting our hypotheses, structural equation models indicated that social avoidance positively predicted concurrent externalizing problems, controlling for shyness, unsociability, and internalizing problems (including depression and anxiety). Findings highlight that socially avoidant adolescents' behaviors may include avoiding others as well as acting out. Longitudinal work is needed to examine the potential bidirectional relations between social avoidance and externalizing problems.